Asuhan Kebidanan Continuity Of Care (COC) Ny.S Pada Keluarga Berencana Gvi Pi1i A2 Di Bpm Megah T.D. Lumbantoruan - Desi Rosmaulina Simarmata; Nurhayati AR; Wartik; Lisa Handayani; Nourma Mahse; Henny Rista; Eka Purnamasari (Medihealth: Jurnal Ilmu Kesehatan dan Sains, 2022)
810 women die due to pregnancy and childbirth. Between 2000 and 2017, the maternal mortality ratio (MMR, 305 maternal deaths per 100,000 live births) fell by approximately 38% worldwide, 94% of all maternal deaths occurring in low and middle income countries. Sub-Saharan Africa and South Asia accounted for about 86% (254,000) of the estimated global maternal deaths in 2017. Sub-Saharan Africa alone accounted for about two-thirds (196,000) of maternal deaths, while South Asia accounted for nearly one-fifth (58,000). Overall, the maternal mortality ratio (MMR) in developing countries has decreased to just under 50%. the author will carry out Continuity of Care care in the work area of the Pratama Madina Tembung Clinic as a place to carry out care that already has a Memorandum of Understanding (MOU) with educational institutions that provide pregnancy services at least 4 times during pregnancy, and strive to meet the 7T standard. The service standards include measuring body weight, measuring height, measuring blood pressure, measuring fundal height, administering Tetanus neonatorium (TT) immunization, administering iron tablets at least 90 tablets during pregnancy, interviews.